2016
DOI: 10.1016/j.jadohealth.2015.09.024
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Examining the Effect of Mindfulness Meditation on Working Memory Capacity in Adolescents

Abstract: This is the first study to provide support for the benefits of short-term mindfulness practice, specifically mindfulness meditation, in improving WMC in adolescents. Results highlight the importance of investigating the components of mindfulness-based interventions among adolescents given that such interventions may improve cognitive function. More broadly, mindfulness interventions may be delivered in an abridged format, thus increasing their potential for integration into school settings and into existing tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
135
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(143 citation statements)
references
References 36 publications
6
135
1
1
Order By: Relevance
“…The lack of time by group interaction is consistent with prior work demonstrating that mindfulness meditation may enhance working memory capacity and functioning, but not consistently differentiate a mindfulness meditation group from an active control group on working memory capacity measures (Banks et al 2015;Jha et al 2010Jha et al , 2017Morrison et al 2014;Mrazek et al 2013;Quach et al 2016). The first potential explanation is that mindfulness meditation does not enhance working memory capacity when controlling for non-specific effects (e.g., engaging in training, expecting improvement).…”
Section: Why Was There No Time By Group Interaction?supporting
confidence: 81%
See 3 more Smart Citations
“…The lack of time by group interaction is consistent with prior work demonstrating that mindfulness meditation may enhance working memory capacity and functioning, but not consistently differentiate a mindfulness meditation group from an active control group on working memory capacity measures (Banks et al 2015;Jha et al 2010Jha et al , 2017Morrison et al 2014;Mrazek et al 2013;Quach et al 2016). The first potential explanation is that mindfulness meditation does not enhance working memory capacity when controlling for non-specific effects (e.g., engaging in training, expecting improvement).…”
Section: Why Was There No Time By Group Interaction?supporting
confidence: 81%
“…The current study investigated if mindfulness meditation could enhance the capacity of the working memory system using recommended rigorous criteria for reaching such a conclusion: using multiple, valid indicators of working memory capacity different from the tasks participants trained on, and demonstrating improvement relative to an active, adaptive control group. This extends previous reports of working memory capacity improvement following mindfulness meditation training by using stringent design criteria that previous studies had not fully incorporated (Banks et al 2015;Jha et al 2010Jha et al , 2017Mrazek et al 2013;Quach et al 2016;Van Dam et al 2017;Zeidan et al 2010). It was hypothesized that the mindfulness meditation group would significantly improve working memory capacity from pretest to posttest, whereas the cognitive training group would not demonstrate such improvement.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In line with this prediction, several prior studies have demonstrated that MT can improve performance on measures of selective and sustained attention (e.g., Allen et al 2012;Jensen et al 2012;Jha et al 2007;MacLean et al 2010;Zanesco et al 2013), and WM (Chambers et al 2008;Jensen et al 2012;Mrazek et al 2013;Quach et al 2016;Van Vugt and Jha 2011;Zeidan et al 2010; but see Morrison et al 2014), and can reduce performance lapses associated with mind wandering Morrison et al 2014;Mrazek et al 2013).…”
mentioning
confidence: 71%